Vodka in pir --- - Podlesnik, Blaž (Slavistična revija, 2017)
The article "The book as a weapon in the case of Zakhar Prilepin" discusses the work of Russian prose writer and journalist Zakhar Prilepin, whose unique understanding of the relationship between literature, reality, and biographical experience generates new insights into the relationship between literature and war. We start by illuminating the author's understanding of "clinical" realism and present Prilepin's military prose as the implementation of the autobiographical hero's model, which establishes his system of values in the chaotic and conflicting reality by joining a male micro-community, marked by the experience of resolving conflicts by means of physical violence. We further argue that Prilepin applies a similar model for constructing identity in his journalism, and that both modes - his literary and media writing - can be viewed as an interesting challenge to the relationship between literature and ethics.
Keywords: 21. st.; ethics; etika; novi realizem; Prilepin, Zahar, 1975-; ruska književnost; ruski pisatelji; Russian literature; vojna proza